Fabrication of advanced bioinspired anisotropic carbide ceramic composites: Past, recent progress, and future perspectives - Huisheng Tian; Li Wang; Buhao Zhang; Xuejian Liu; Jie Yin; Zhengren Huang (Journal of Advanced Ceramics)
Advances in the study of structural ceramic materials have revealed new perspectives and opportunities, with an increasing emphasis on incorporating biomimicry concepts. Carbide ceramics with anisotropic crystal structures—such as silicon carbide—exhibit superior properties, including high modulus, high-temperature resistance, wear resistance, and high thermal conductivity, making them ideal structural materials. The implementation of biomimetic texturing techniques can enhance their performance along specific orientations, thereby expanding their potential for use in more rigorous environments and endowing them with integrated structural and functional characteristics. This review provides an overview of commonly textured biological materials and discusses their performance. It emphasizes the techniques used to prepare anisotropic carbide ceramics and anisotropic carbide ceramic composites—such as strong external field induction (hot working under uniaxial pressure, casting technologies within magnetic alignment, etc.), template methods (biotemplating, ice templating, etc.), and three-dimensional printing technologies (direct ink writing, stereolithography, etc.)—focusing on the work of researchers within the structural ceramic community, summarizing the current challenges in the preparation of anisotropic carbide ceramic composites, and providing insight into their future development and application.